The application of halal in supply chain management: principles in the design and management of halal food supply chains / Marco Tieman - Marco, Tieman (Institute of Graduate Studies, UiTM, 2013)
Muslims want assurance that the food they consume is a true manifestation of Islamic principles. Important questions halal certified food manufacturers have today are whether and how to start with halal supply chain management in protecting the integrity for the Muslim consumer and protecting their brand. The research problem can be defined as following: How to optimise halal food supply chains for certain productmarket combinations? The aim of the research is to contribute to the body of knowledge on supply chain management by identifying the principles in the design and management of halal food supply chains. As halal supply chain management is a new phenomenon, the core of this research has an exploratory and qualitative approach, through in-depth interviews, a large discussion group and focus groups. However, in measuring the perception of the Muslim consumer, a consumer survey has been used…